A Latent Class Analysis of Perceived Barriers to Help-seeking Among People with Alcohol Use Problems Presenting for Telephone-delivered Treatment. (30th November 2022) - Grigg, Jasmin; Manning, Victoria; Cheetham, Ali; Youssef, George; Hall, Kate; Baker, Amanda L; Staiger, Petra K; Volpe, Isabelle; Stragalinos, Peta; Lubman, Dan I
Abstract: Aims: Despite the magnitude of alcohol use problems globally, treatment uptake remains low. This study sought to determine the proportion of people presenting to telephone-delivered alcohol treatment who are first-time help-seekers, and explored perceived barriers to help-seeking to understand the barriers this format of treatment may help to address. Methods: Secondary analysis of baseline data from a randomized controlled trial of a telephone-delivered intervention for alcohol use problems. Latent class analysis (LCA) identified participant profiles according to self-reported barriers to alcohol treatment. Results: Participants' (344) mean age was 39.86 years (SD = 11.36, 18–73 years); 51.45% were male. Despite high alcohol problem severity (Alcohol Use Disorder Identification Test: mean = 21.54, SD = 6.30; 63.37% probable dependence), multiple barriers to accessing treatment were endorsed (mean = 5.64, SD = 2.41), and fewer than one-third (29.36%) had previously accessed treatment. LCA revealed a two-class model: a 'low problem recognition' class (43.32%) endorsed readiness-for-change and attitudinal barriers; a 'complex barriers' class (56.68%) endorsed stigma, structural, attitudinal and readiness-to-change barriers, with complex barrier class membership predicted by female sex (adjusted OR = 0.45, 95% CI 0.28, 0.72) and higher psychological distress (adjusted OR = 1.13, 95% CI 1.08, 1.18). Conclusion: The majority of people accessing this telephone-delivered intervention were new to treatment, yet had high alcohol problem severity. Two distinct profiles emerged, for which telephone interventions may overcome barriers to care and tailored approaches should be explored (e.g. increasing problem awareness, reducing psychological distress). Public health strategies to address stigma, and raise awareness about the low levels of drinking that constitute problem alcohol use, are needed to increase help-seeking. Abstract : Short Summary: Most people accessing telephone-delivered treatment for alcohol use problems were new to treatment. Latent class analysis identified two profiles regarding barriers to help-seeking, a 'low problem recognition' class, and a 'complex barriers' class (predicted by female sex and higher psychological distress), for which telephone interventions may help to overcome barriers to care.